Complete Systematic Land Registration (PTSL) Services at The National Land Agency Office Gowa Regency - Nurul Amelia Usman; Herlina Sakawati; Muh Nur Yamin (Perkembangan Kajian Sosial, 2026)
This study aims to determine how the Complete Systematic Land Registration (PTSL) service is carried out at the National Land Agency (BPN) Office in Gowa Regency, South Sulawesi Province, Indonesia. This study used a qualitative, descriptive approach. Data were collected through observation, in-depth interviews, and documentation studies. The research subjects consisted of BPN Gowa Regency officials directly involved in PTSL services as well as community service recipients. The data analysis techniques used in this study were data condensation, data presentation, conclusion drawing, and verification. The results showed that the PTSL service at the BPN Gowa Regency Office has been running well by applying the principles of convenience, efficiency, effectiveness, accuracy, user-orientedness, and legal compliance. The program's success is supported by a one-stop service system, the use of technology, and collaboration between the BPN, local governments, and the community. Although still facing administrative and technical obstacles, the PTSL service has been able to increase community participation, accelerate land certification, and provide legal certainty regarding land ownership rights. These findings indicate that PTSL services in Gowa Regency have met the SERVQUAL (service quality) dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy, and reflect the principles of good governance in the implementation of public services. Thus, PTSL in Gowa Regency is able to provide fast, transparent, and legally valid land certification services.